2020
DOI: 10.6061/clinics/2020/e1845
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress as a Risk Factor for Hearing Changes in HIV-positive Normal Listeners

Abstract: Human immunodeficiency virus-positive (HIV+) individuals can experience a decrease in antioxidants. Such deficiency can make inner ear cells and synapses more vulnerable to oxidative stress, resulting in auditory alterations, even in the presence of normal thresholds. This study aims to compare the audiological findings of HIV+ patients (with and without exposure to anti-retroviral treatment) to those of healthy individuals. METHODS: This was a cross-sectional observational study, comprising 42 normal-hearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Although this procedure might have compromised the p-values calculated in the present study due to a possible violation of the assumption of independence of observations, it may be an interesting move in order to reduce the number of measures to be analyzed in clinical practice and to increase statistical power of the sample. It is also worth noting that grouping the ears together is a data analysis procedure used in other studies in the audiology field (e.g., [ 60 , 61 , 62 , 63 , 64 ]). Another limitation might be the predominance of female subjects in our sample, although previous research found no difference between genders regarding BMT performance [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although this procedure might have compromised the p-values calculated in the present study due to a possible violation of the assumption of independence of observations, it may be an interesting move in order to reduce the number of measures to be analyzed in clinical practice and to increase statistical power of the sample. It is also worth noting that grouping the ears together is a data analysis procedure used in other studies in the audiology field (e.g., [ 60 , 61 , 62 , 63 , 64 ]). Another limitation might be the predominance of female subjects in our sample, although previous research found no difference between genders regarding BMT performance [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although combined antiretroviral therapy (cART) cannot totally remove viral proteins from the brain, it can systemically limit viral replication and partially restore immunological functions. [2] Prior research suggested that individuals with HIV-associated neurocognitive disorders exhibit dysfunction in high-order cognitive processes like attention/working memory, abstract/executive control, memory (learn and recognition), and speed of information processing in addition to low-level sensory processing [3][4][5]. [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that otitis media can cause temporary hearing loss and must be treated at the periphery so that adequate medical treatment can be instituted. These individuals may also exhibit cochlear pathology/inner ear disorders due to direct viral action and use of antiretroviral drugs and/or potentially ototoxic drugs, which can cause sensorineural hearing loss (Carla G Matas et al 2020).…”
Section: Introductionmentioning
confidence: 99%